Outcomes in Eyes with Retinal Angiomatous Proliferation in the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT) - Daniel, Ebenezer; Shaffer, James; Ying, Gui-shuang; Grunwald, Juan E; Martin, Daniel F; Jaffe, Glenn J; Maguire, Maureen G (Ophthalmology (Rochester, Minn.), 2016)
To compare baseline characteristics, visual acuity (VA), and morphologic outcomes between eyes with retinal angiomatous proliferation (RAP) and all other eyes among patients with neovascular age-related macular degeneration (NVAMD) treated with anti-vascular endothelial growth factor (VEGF) drugs. Prospective cohort study within the Comparison of Age-Related Macular Degeneration Treatments Trials (CATT). Patients with NVAMD. Reading center staff evaluated digital color fundus photographs, fluorescein angiography (FA) images, and optical coherence tomography (OCT) scans of eyes with NVAMD treated with either ranibizumab or bevacizumab over a 2-year period. Retinal angiomatous proliferation was identified by the intense intra-retinal leakage of fluorescein in combination with other associated features. Visual acuity; fluorescein leakage; scar; geographic atrophy (GA) on FA; retinal thickness, fluid, and subretinal hyperreflective material (SHRM) on OCT; and the number of intravitreal anti-VEGF injections at 1 and 2 years. Retinal angiomatous proliferation was present in 126 of 1183 (10.7%) study eyes at baseline. Mean VA improvement from baseline was greater (10.6 vs. 6.9 letters; P = 0.01) at 1 year, but similar at 2 years (7.8 vs. 6.2 letters; P = 0.34). At 1 year, eyes with RAP were more likely to have no fluid (46% vs. 26%; P < 0.001) on OCT, no leakage on FA (61% vs. 50%; P = 0.03), and greater reduction in foveal thickness (-240 μm vs. -161 μm; P < 0.001). They were more likely to demonstrate GA (24% vs. 15%; P = 0.01) and less likely to have scarring (17% vs. 36%; P < 0.001) or SHRM (36% vs. 48%; P = 0.01). These results were similar at 2 years. The mean change in lesion size at 1 year differed (-0.27 DA vs. 0.27 DA; P = 0.02), but was similar at 2 years (0.49 DA vs. 0.79 DA; P = 0.26). Among eyes treated PRN, eyes with RAP received a lower mean number of injections in year 1 (6.1 vs. 7.4; P = 0.003) and year 2 (5.4 vs. 6.6; P = 0.025). At both 1 and 2 years after initiation of anti-VEGF treatment in CATT, eyes with RAP were less likely to have fluid, FA leakage, scar, and SHRM and more likely to have GA than eyes without RAP. Mean improvement in VA was similar at 2 years.